THE RULERS OF GERMAN AFRICA 1884-1914 - Cornwell, Richard (Scientia Militaria - South African Journal of Military Studies, 2011)
This book is described by the authors in their preface as ’the first in a multi-volume work designed to elucidate the sociological and functional characteristics, the achievements as well as the shortcomings, of the white empire builders, civilian and military, during the age of the ’New Imperialism’ in Africa.’